2014
DOI: 10.1007/s11203-014-9094-5
|View full text |Cite
|
Sign up to set email alerts
|

Central limit theorems for empirical product densities of stationary point processes

Abstract: We prove the asymptotic normality of kernel estimators of second-and higher-order product densities (and of the pair correlation function) for spatially homogeneous (and isotropic) point processes observed on a sampling window W n which is assumed to expand unboundedly in all directions as n → ∞ . We first study the asymptotic behavior of the covariances of the empirical product densities under minimal moment and weak dependence assumptions. The proof of the main results is based on the Brillinger-mixing prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…The authors often observed such a behavior in their statistical work and believe that it is a somewhat intuitive knowledge in the statistical community. Fortunately, there is theoretical work on central limit theorems which confirms these empirical findings and gives them a theoretical explanation for spatially homogeneous (and isotropic) point processes (Heinrich and Klein , Heinrich ).…”
Section: Methodsmentioning
confidence: 78%
“…The authors often observed such a behavior in their statistical work and believe that it is a somewhat intuitive knowledge in the statistical community. Fortunately, there is theoretical work on central limit theorems which confirms these empirical findings and gives them a theoretical explanation for spatially homogeneous (and isotropic) point processes (Heinrich and Klein , Heinrich ).…”
Section: Methodsmentioning
confidence: 78%
“…In that case, we do not require further assumptions on scriptDn. However, in applications dealing with kernel estimators depending on a bandwidth h n tending towards 0, we may have Var0.1emTWnfalse(boldXfalse) of the order false|Wnfalse|hnd (e.g., Heinrich & Klein, ). Then, ( scriptH4) can be fulfilled if s n =1/ h n and η >0 so that, by ( scriptH2), false|scriptDnfalse| is also of the order false|Wnfalse|false/sn.7ptd=false|Wnfalse|hnd.…”
Section: Central Limit Theorem Based On Bolthausen's Approachmentioning
confidence: 99%
“…For Brillinger-mixing PPs, various CLTs have been proved in [9], [10] for both the estimators (4.3) and (4.4). These results permit us to establish asymptotic χ 2tests to check hypotheses about the second product densities and pair correlation functions.…”
Section: Some Applications To Statistical Second-order Analysis Of Stmentioning
confidence: 99%
“…In our situation, these tests can be reformulated for testing hypotheses about the function |C 0 (x)| or its isotropic counterpart |c(r)| = |C 0 (x)| for r = x . The following limit theorem (formulated as Theorems 3.3 and 4.1 in [10] in a more general setting) provide the basis for these tests. and |W n |( λ n − C 0 (o)) is asymptotically normally distributed with mean zero and variance σ 2 = C 0 (o) + α R d |C 0 (x)| 2 dx (by Corollary 2), see also [25] for α = −1.…”
Section: Some Applications To Statistical Second-order Analysis Of Stmentioning
confidence: 99%
See 1 more Smart Citation